Mouzinho da Silveira or the Unforeseen Revolution - Costa,Fernando Dores (2022)
Abstract Alexandre Herculano stated that Mouzinho da Silveira was a superior and even brilliant man for the reason that he was a verb; the incarnation of an idea, the personification of a great social fact. This great fact is what was called, in the interpretive framework inspired by the French Revolution, the abolition of “feudalism” in Portugal, a profound social change. However, the scope and consequences of the law of forais were unexpected and not the result of a project.